2020
DOI: 10.1113/jp279876
|View full text |Cite
|
Sign up to set email alerts
|

Lower body negative pressure protects brain perfusion in aviation gravitational stress induced by push–pull manoeuvre

Abstract: Rapid alterations of gravitational stress during high-performance aircraft push-pull manoeuvres induce dramatic shifts in volume and pressure within the circulation system, which may result in loss of consciousness due to the rapid and significant reduction in cerebral perfusion. There are still no specific and effective countermeasures so far. r We found that lower body negative pressure (LBNP), applied prior to and during −Gz and released at the subsequent transition to +Gz, could effectively counteract grav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
24
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 27 publications
0
24
1
2
Order By: Relevance
“…In this issue of The Journal of Physiology , Xing et al . (2020) implemented an elegant and straightforward strategy for preserving cerebral perfusion during the push–pull manoeuvre. As moderate levels of lower body negative pressure (LBNP) redistributes blood volume without affecting arterial pressure, Xing et al .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In this issue of The Journal of Physiology , Xing et al . (2020) implemented an elegant and straightforward strategy for preserving cerebral perfusion during the push–pull manoeuvre. As moderate levels of lower body negative pressure (LBNP) redistributes blood volume without affecting arterial pressure, Xing et al .…”
mentioning
confidence: 99%
“…As moderate levels of lower body negative pressure (LBNP) redistributes blood volume without affecting arterial pressure, Xing et al . (2020) measured systemic and cerebral haemodynamics during a simulated push–pull manoeuvre at two levels of hypogravity (−0.50 G and −0.87 G), with and without (control) application of LBNP at −40 mmHg. Two variations of the push phase consisted of a head down tilt (HDT) at −30° or −60° corresponding to −0.50 G or −0.87 G, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Xing and colleagues found that pulsatility index (PI) was lower in LBNP bouts during the HDT–HUT transition period (Xing et al . 2020). Increases in PI during HDT indicates vasoconstriction of cerebral resistance vessels, which occurs as a result of the hydrostatic pressure gradient mentioned above.…”
mentioning
confidence: 99%
“…A recent publication by Xing et al . (2020) in The Journal of Physiology examines an alternative strategy to counteract the negative haemodynamic effects of PPM by incorporating lower body negative pressures (LBNP) in a simulated PPM environment.…”
mentioning
confidence: 99%